Safety of combined PD‐1 pathway inhibition and radiation therapy for non‐small‐cell lung cancer: A multicentric retrospective study from the GFPC. (11th October 2018) - Lesueur, Paul; Escande, Alexandre; Thariat, Juliette; Vauléon, Enora; Monnet, Isabelle; Cortot, Alexis; Lerouge, Delphine; Danhier, Serge; Dô, Pascal; Dubos‐Arvis, Catherine; Chouaïd, Christos; Gervais, Radj
Abstract: Introduction: Randomized prospective studies on patients with metastatic non‐small‐cell lung cancers (NSCLCs) showed that anti‐programmed death‐1 (PD‐1) agents notably improved 2‐year overall survival (OS) rates, compared to docetaxel. NSCLC patients now receive nivolumab and irradiation, concurrently or not. However, little is known about the safety of this combination, even though the preclinical model suggested a possible synergic effect. We analyzed NSCLC patients treated with radiotherapy and nivolumab according to former's timing. Methods: We retrospectively reviewed records of a large series of metastatic NSCLC patients from three French centers, irradiated during the 6 months preceding, concomitantly, or 3 months after nivolumab administration to assess nivolumab tolerance and outcomes. Results: Among 104 patients included (37 women; 67 men; median age 60.3 years; 67% with performance status <2; 93.2% were current or past smokers) and their 144 intra‐ or extracranial irradiation courses, any‐grade adverse events (AEs) were observed in 62 (59.6%), with 10 (9.6%) experiencing at least one grade 3/4 toxicity and 9 (8.7%) at least one grade 3/4 immune‐related AE (IRAE). Respective 1‐ and 2‐year OS rates were 48.8% and 29.1%, while 1‐ and 2‐year progression‐free survival (PFS) rates were 20.9% and 10.1%. PFS was significantly better for patients with IRAE(s) ( P  = 0.038) than those without and a trend toward better OS ( P  = 0.06). Delivering radiation before or during/after nivolumab administration was not associated with better OS or PFS. Conclusion: Radiotherapy delivered during the 6 months before, during, or the three months following nivolumab for NSCLCs was not associated with an increased risk of severe or unexpected toxicities. Abstract : The largest series reporting the safety of nivolumab and radiotherapy combination. The combination of nivolumab and radiotherapy for NSCLC is safe, and the therapeutic sequence has no impact on toxicity rate. PFS is significantly better for patients with immune‐related adverse events.